2020
DOI: 10.3390/neurolint12030015
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Physical Therapy and Polymyositis/Dermatomyositis—A Systematic Review of the Literature

Abstract: Objective: to find the most up-to-date evidence of the effectiveness and safety of supervised physical therapy in polymyositis/dermatomyositis patients. Methods: a systematic review of the literature in the main scientific databases was carried out. We searched for randomized controlled trials concerning supervised physical therapy and polymyositis/dermatomyositis. The PICOS method was used for the formulation of the clinical query. Methodological quality and the level of evidence of the included studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…The institution of an early rehabilitation program appears to have beneficial effects, with a positive impact on functionality and independence. This fact contradicts the classic belief that performing exercise may enhance muscle inflammation and increase CK levels, aggravating muscle weakness and fatigue [1,4]. The increase in CK blood levels with consequent normalization after 24 hours is a normal acute response to exercise, but there are no studies that support this idea [4].…”
Section: Safety Of Rehabilitationmentioning
confidence: 90%
See 4 more Smart Citations
“…The institution of an early rehabilitation program appears to have beneficial effects, with a positive impact on functionality and independence. This fact contradicts the classic belief that performing exercise may enhance muscle inflammation and increase CK levels, aggravating muscle weakness and fatigue [1,4]. The increase in CK blood levels with consequent normalization after 24 hours is a normal acute response to exercise, but there are no studies that support this idea [4].…”
Section: Safety Of Rehabilitationmentioning
confidence: 90%
“…According to some studies, exercise increases the performance of patients with DM by improving aerobic muscle metabolism [1,4,[10][11][12][13][14] increasing maximum VO 2 values, and improving mitochondrial enzymatic activity and oxygen supply from the skeletal muscle. In one of these studies, Munter et al [11] found that there was an activation of the aerobic phenotype and a decreased inflammatory response, through the positive regulation of molecular pathways involved in aerobic capacity, muscle remodeling, and increased capillary density, improved mitochondrial function, and ATP production.…”
Section: Performance and Aerobic Functionmentioning
confidence: 99%
See 3 more Smart Citations